(untitled) (Diametros, 2024)
The importance of ethics in social research has increased in recent years, something reflected, among other things, in the progressive codification and institutionalization of research ethics and the growing literature on this topic. We argue that despite increasing ethical regulation and ethical reflection in social research, ethical challenges also arise, i.e., difficult situations connected with selecting ethically appropriate behavior. The aim of this special issue is to invite social researchers to reflect upon and discuss ethical challenges in contemporary social research. The contributions in this issue concern vulnerability (one critically analyzing it, and another adapting the vulnerability concept to conducting research with people after a laryngectomy), the researcher and participant relationship, research ethics in multilingual world, and the ethicality of data representation where language plays a particular role in creating a form of activist research.